Itinéraires militants contestés dans le mouvement occitan : le cas de Poble d’Oc - Guillaume Genoud (Lengas)
The occitanist organisation Poble d'Oc remains little known. In particular, its political stance is unclear, with some studies linking it to anarchism and others emphasising its links with the radical right. This article shows that Poble d'Oc's links with the radical right have been exaggerated by its political opponents, but that the trajectory of its founders nonetheless allows us to learn more about the movement of activists between the right and the left during the 68s.